Commited to flying high in the lowcost airline industry? An extrinsic and intrinsic motivation approach / Rasmee Islam, Ann Suwaree Ashton and Anderson Ngelambong - Islam, Rasmee; Ashton, Ann Suwaree; Ngelambong, Anderson (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
This paper aims to investigate the linkages between motivation factors, job satisfaction and employee commitment in a low-cost airlines company. A quantitative approach was employed using a random survey questionnaire to collect data from low-cost airline ground staff. A total of 400 samples were received, and multiple regression with the stepwise method was used to perform a study on the relationship between variables. The results revealed that intrinsic motivation was positively related to job satisfaction, of which the most influencing factors were recognition, work itself, advancement and responsibility. Secondly, the extrinsic motivation factors (salary, technical supervision, working conditions, company policy and administration, and job security) were found to be related to job satisfaction. Furthermore, the study found that job satisfaction was related to employee commitment to work in a low-cost carrier company. The study suggested that the organization should focus on improving staff job satisfaction as it helps them to be committed to the airline organization. Several academic and managerial contributions are put forward, and future research is also recommended at the end of the paper.